The philosophy of positive law foundations of jurisprudence - Murphy, James Bernard, 1958- (New Haven, Conn. ; London : Yale University Press, 2005)
James Bernard Murphy uncovers a fundamental continuity among four legal philosophers: Plato, Thomas Aquinas, Thomas Hobbes and John Austin. He argues that, in their theories of positive law, they represent successive chapters in a single story.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Legal positivism; Law; Jurisprudence & general issues; Methods, theory & philosophy of law